Assessing the integration of senior living technology in Malaysian real estate developments - Ong, Magdelyn Ley Sim (2025)
The rapid aging of Malaysia’s population presents significant challenges to traditional housing and eldercare systems. Senior living technologies, including smart home systems, health monitoring devices, and telehealth platforms, have emerged as promising solutions to enhance the quality of life, safety, and independence of older adults. This study explores the integration of senior living technologies in Malaysian real estate developments, focusing on their adoption, associated challenges, and impact on senior residents. Employing a qualitative and exploratory research design, semi-structured interviews were conducted with real estate developers, industry experts, and policymakers to uncover insights into the motivations, barriers, and outcomes associated with these technologies. Key findings reveal critical barriers such as financial constraints, regulatory gaps, cultural resistance, and infrastructure disparities, alongside transformative benefits in safety, health, and social connectivity. The study identifies the need for targeted strategies, including public-private partnerships, regulatory reforms, and culturally sensitive, cost-effective solutions to advance the adoption of senior living technologies in Malaysia. These insights provide a foundation for designing inclusive, technology-enabled environments that cater to the needs of Malaysia’s aging population, contributing to sustainable societal development.